Cadê o sujeito que estava aqui? Contribuições da psicanálise sobre a permanência das pessoas em situação de rua no campo da política de assistência social - Larissa Ferreira Dias Leite (2021)
The phenomenon of people on the trajectory of life on the streets is a complex, multi-causal issue and is in visible expansion. The present presented here proposes to discuss about this issue in the scope of the Unified Social Assistance System (SUAS) and about the possible contributions of psychoanalysis in this context. Thus, a movement of reflection begins: at what point does the subject have space in public policy? Who is he and what makes him look for the street and stay there? How can psychoanalysis help to understand this phenomenon and what are the possible interventions? Therefore, the objective was to understand the circumstances involved in the trajectory of life on the streets of the interviewed subjects, considering the subjective aspects of staying in this condition. That is, through semi-structured qualitative interviews, analyze the reasons, in addition to those that make the subjects seek the street, those that make them stay there. Furthermore, it seeks to understand the reasons and facilitators of those who have been on the streets and who are no longer in this condition, and the facilitators who allowed them to get out of this situation. Therefore, in addition to some psychoanalytic assumptions, semi-structured interviews were carried out with 5 subjects, 2 who were homeless at the time of the research, 2 who were no longer in this condition and 1 who remained on the path house-street. Finally, the purpose of this study is to move towards a twist of perspective, starting from the subjects, the users, towards the SUAS offers, not the other way around. Emphasizing the importance of a singular look at the issue, since the tone of the follow-up, of the conduct of the case, is established in the transference relationship. Perhaps in this way, understanding such nuances (also of a subjective order?), betting on the need for listening and the emergence of the subject, we can contribute to the improvement of offers aimed at people on the street. That one can find, at the 'end' of the work, lights on the way that can be captured by politics and placed to illuminate steps ahead.